Dynamic Simulation of the Effect of Discharge Rate Variations on Tailing Thickener Behavior of the Coal-Washing Plant. Issue 2 (3rd March 2016) - Rahimi, Mehdi; Rezai, Bahram; Abdollahzadeh, Ali A.
ABSTRACT: Dynamic simulation approach can be used for understanding the nonlinear behavior in mineral processing circuits. In this study, the dynamic simulation was carried out for the thickener of the Tabas coal-washing plant at different conditions and the effect of discharge rate variations on the solid volume fraction of the thickener under flow and mudline height was investigated. It was observed that for the conditions that the solid volume fraction of the thickener underflow is higher and the midline height is lower, the time to reach the steady state condition is higher. It was also observed that the maximum solid volume fraction of the thickener underflow decreases and the mudline height increases with pH reduction. Also, the maximum solid volume fraction of the thickener underflow decreases and the mudline height increases with particle size reduction at certain pH and flocculant dosage values.